Literature on Student Book and its Effect for Developing Elementary School Teaching Materials - Ningrum, Emi Febrina (Bina Nusantara University, 2018)
This research adopted the qualitative research content analysis on the 4th grade of elementary school students which aimed to know the literary material contained in the 2013 curriculum student book in Indonesia as the compulsory guidebook. The results of this research could be useful for guidelines for the development of literary materials by teachers when implementing learning planning. The findings show that students’ literature material is only about 30% of the Indonesian language learning material found in the 4th grade of elementary school. The lesson was limited to reading the text of the story then answering questions about the content of the text. In general, literary competence material in student books has not been emphasized on the cultivation of literary concepts. The development of literary materials in the 4th grade of elementary school should include the introduction of literary concepts, analyzing the contents of literary texts, and applying moral values in literature to be applied in daily life.